Upaya Pendidik Dalam Meningkatkan Kepercayaan Diri Pada Anak Generasi Z Di Era Persebaran Informasi Yang Pesat Di Instagram Melalui Penerapan Teori Behavioristik - Midhfara Khumayra Anang (Departement of Mathematics Education, 2023)
The development of information technology, such as social media, has had a significant impact on the development of Generation Z. The era of rapid dissemination of information on social media, especially Instagram, has brought about a major change in how Generation Z children understand and shape their self-image. One of the issues of concern is the level of confidence in Generation Z children. This paper aims to explore the impacts of Instagram that can be made to enhance the confidence of Generation Z children in the information dynamics of social media. The study will involve qualitative approaches using observation and analysis of social media content. The study will focus on understanding how Generation Z children interact with information on social media and how it affects their self-perception. The paper will also present practical recommendations for educators to effectively support developing confidence among Generation Z children in this era through the application of behavioristic.